The Effect of Company Growth, Asset Structure, Non-Performing Loans, Bank Profitability And Cash Ratio On Debt To Equity Ratio At PT. BPR Bank Nusamba Pecangaan - Fauzuna Naufal Wijanarko (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
The purpose of this study is to analyze company growth, asset structure, non-performing loans, bank profitability, and cash to debt to equity ratio at PT. BPR Bank Nusamba Pecangaan. Bank debt management is a major responsibility in banking. Failure in debt management can lead to decreased profitability, the impact of high operational costs, and liquidity risk. The method used is a descriptive associative research method with a quantitative approach. The population used is PT. BPR Nusamba Pecangaan with a quarterly period of 2020 to 2023. Data collection techniques use secondary data through documentation and literature studies with the Purposive Sampling method. The results of this study indicate that company growth, asset structure, non-performing loans, bank profitability, and cash ratio have a significant influence simultaneously on DER. Partially, company growth has a positive relationship and a significant influence on DER. On the other hand, asset structure and bank profitability have a positive but insignificant relationship to DER. Meanwhile, non-performing loans and cash ratio have a negative and insignificant relationship to DER at PT BPR Nusamba Pecangaan.